IMPLEMENTASI KINERJA KARYAWAN PADA PT MITRA LAUTAN MINA SUKSES DI DKI JAKARTA - Agustin Suharjo, Ayu; Krisyanto, Edy (Journal of Research and Publication Innovation, 2024)
An organization, whether business or non-business, cannot be separated from the role of Human Resources (HR) management. The more the organization or company develops, the more it involves workers in an effort to support the smooth running of the organization or company. To provide good product quality, the company must be able to improve and maximize employee performance, the company needs to pay attention to the needs of employees in working because by fulfilling the needs of its employees, the company will get better work quality or employee performance and the quality of the products created or worked on with good performance, the quality of the products worked on will be good or satisfactory. Indicators that must be met are the physical work environment, non-physical work environment, compliance with company regulations, work quality, work quantity, responsibility, cooperation and initiative. Overall, all of these indicators must be met by employees and the company optimally in order to achieve the desires of employees and the company in the future.